Ankylosis of the spine in a case with ochronosis - (:unkn) unknown (My University, 2003)
A thirty-nine-year-old man presented with a complaint of low back pain with a history of 20 years. Cervical and thoracolumbar radiographs showed wide calcification areas and ankylosis in the intervertebral discs. Observation of blue-gray pigmentation around his nose and ears suggested a diagnosis of ochronosis, which was confirmed by the detection of high levels of homogentisic acid in the urine and dark urine color following alkalization. Ochronosis should be included in the differential diagnosis in patients with chronic low back pain, calcified intervertebral discs, and black pigmentation in cartilagenous and collagenous tissues.
Keywords: Adult; Humans; Male; Radiography; Diagnosis, Differential; Lumbar Vertebrae; Calcinosis; Low Back Pain; Homogentisic Acid; Ochronosis; Ankylosis